(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Endometrial cancer is one of the most common gynecological malignancies worldwide, with its incidence closely associated with metabolic disorders. Metabolic syndrome, characterized by obesity, insulin resistance, dyslipidemia, and hypertension, has been identified as a significant risk factor influencing the development, progression, and prognosis of endometrial cancer. This article examines the impact of metabolic syndrome on the clinical course and outcomes of endometrial cancer, focusing on underlying biochemical mechanisms and current therapeutic approaches. Evidence suggests that metabolic syndrome contributes to tumor progression through hormonal imbalance, chronic inflammation, and altered metabolic signaling pathways. Understanding these interactions is essential for improving prognosis and developing individualized treatment strategies for patients with endometrial cancer.